INFOGEST Digestion Assay of Raw and Roasted Hazelnuts and Its Impact on Allergens and Their IgE Binding Activity - Ivana Prodić; Katarina Smiljanić; Christoph Nagl; Barbara Ballmer-Weber; Karin Hoffmann-Sommergruber; Tanja Ćirković Veličković (Foods, 2022)
Most of the food allergens sensitized via the gastrointestinal tract resist thermal treatments and digestion, particularly digestion by pepsin. Roasted hazelnuts are more commonly consumed than raw ones. Since no studies have characterized gastric digestion protein fragments of raw and roasted hazelnuts nor their IgE binding properties, we compared these aspects of raw and roasted hazelnuts’ gastric digesta obtained by INFOGEST protocol. Their electrophoretically resolved profiles were probed with hazelnut allergic patients’ sera in 1D and 2D immunoblots. Electrophoretic profiles demonstrated pepsin digestion of all hazelnut allergens to varying extents. While 2D immunoblots indicated that roasting slightly reduced allergenicity, IgE ELISA with the pool of sera showed a slight significant (10%) increase in IgE binding in both gastric digesta. Cor a 9 isolated from the raw and roasted hazelnuts, characterized by far and near CD, remained stable after roasting, with preserved IgE reactivity. Its immunoreactivity contribution by inhibitory ELISA was noticeable in raw and roasted hazelnut digesta; its activity was slightly stronger in the roasted preparations. Roasting has a visible impact on proteins; however, it did not affect overall IgE reactivity. Gastric digestion slightly increases the overall IgE reactivity in raw and roasted hazelnuts, and may therefore impact the profiles of allergens and their fragments available to interact with the immune system in the small intestine.